Relationship between physiological off-ice testing, on-ice skating, and game performance in Division I female ice hockey players - Boland, M.; Delude, K.; Miele, E. M. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to identify off-ice testing variables that correlate with skating and game performance in Division I collegiate female ice hockey players. Twenty female forward and defensive players (19.95 ± 1.35 years) were assessed for mass, height, percent fat mass (%FAT), bone mineral density, predicted 1 repetition maximum (RM) absolute and relative (REL%) bench press (BP) and hex bar deadlift (HDL), lower-body explosive power, anaerobic power, countermovement vertical jump, maximum inspiratory pressure (MIP), and on-ice repeated-skate sprint (RSS) performance. The on-ice RSS test included 6 timed 85.6-m sprints with participants wearing full hockey equipment; fastest time (FT), average time (AT), and fatigue index (FI) for the first length skate (FLS; 10 m) and total length skate (TLS; 85.6 m) were used for analysis. Game performance was evaluated with game statistics: goals, assists, points, plus-minus, and shots on goal (SOG). Correlation coefficients were used to determine relationships. Percent fat mass was positively correlated (p = 0.05) with FLS-FI and TLS-AT; TLS-FT was negatively correlated with REL%HDL; BP-RM was negatively correlated with FLS-FT and FLS-AT; MIP positively correlated with assists, points, and SOG; FLS-AT negatively correlated with assists. Game performance in female ice hockey players may be enhanced by greater MIP, repeat acceleration ability, and mode-specific training. Faster skating times were associated with lower %FAT. Skating performance in female ice hockey players may be enhanced by improving body composition, anaerobic power, and both lower- and upper-body strength in off-ice training.